2012
DOI: 10.1007/s00167-012-2094-3
|View full text |Cite
|
Sign up to set email alerts
|

Do patients benefit from tourniquet in arthroscopic surgeries of the knee?

Abstract: Therapeutic randomized controlled trials, Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Considering almost all RCTs included supported that there was no statistically significant difference in the operative time between the tourniquet group and the nontourniquet group, we preferred that not using the tourniquet during the operation did not contribute to a longer operation time. These results were also consistent with previous meta-analysis 12 which suggested that there was no significant difference in visualization and operative time between the tourniquet and the nontourniquet groups. We also found that arthroscopy without tourniquet was associated with less blood loss in the drain than tourniquet group postoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…Considering almost all RCTs included supported that there was no statistically significant difference in the operative time between the tourniquet group and the nontourniquet group, we preferred that not using the tourniquet during the operation did not contribute to a longer operation time. These results were also consistent with previous meta-analysis 12 which suggested that there was no significant difference in visualization and operative time between the tourniquet and the nontourniquet groups. We also found that arthroscopy without tourniquet was associated with less blood loss in the drain than tourniquet group postoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…25 Tourniquet use is thought to allow improved visibility and reduce operative time. However, this has not been demonstrated in well-designed clinical studies on ankle arthroscopy.…”
Section: Pitfallsmentioning
confidence: 99%
“…Nonetheless, like other surgical techniques, tourniquet can also cause different complications [11] such as neurovascular injuries, deep vein thrombosis, edema, bruising, rhabdomyolysis, pulmonary embolism, acute pulmonary edema, cardiac arrest, increased postoperative bleeding, hypoxia of skin flaps, delayed wound healing, muscular ischemia, delayed reversal of muscular strength due to microscopic alterations of myofibrils [12], limited range of motion (ROM), and high levels of postoperative pain [10]. Ischemic or compressive effects of tourniquet can alter neural conduction and muscular function and cause a wide spectrum of complications from mild transient dysfunction to irreversible damages [13].…”
Section: Introductionmentioning
confidence: 99%